Registration and Licensure of Nutrition Professionals in Florida - Linda B. Bobroff (EDIS)
Consumers need to know who is qualified to practice nutrition or dietetics before seeking nutrition advice. This 3-page fact sheet is a major revision that provides information about dietetic registration and licensure. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, June 2016.